DECREASE IN FREE FATTY ACID CONTENT AND COLOR AT USED COOKING OIL WITH ACTIVATED CARBON OF REEDS (Imperata cylindrica L. Raeusch) - Samsuar Samsuar (JFL : Jurnal Farmasi Lampung, 2019)
Cooking oil is one of the foods that are needed by the community in daily life. The use of cooking oil continuously at high temperatures, produces cooking oil that is no longer feasible to use. Therefore, it’s necessary to purify used cooking oil so that it can be reused for non-foood purposes such as making soap or biodiesel fuel. This purification process is utilie the activated carbon of reeds (Imperata cylindrica L. Raeusch) as an adsorbent to reduce the levels of free fatty acids and colors in used cooking oil. Free fatty acid content test using acid base titration method and color change using Uv-Vis spectrofotometry method. This study aims to determine the optimum concentration of reeds activated carbon as an adsorbent in reducing the levels of free fatty acids and colors in used cooking oil, which consists of the concentration of reeds activated carbon which is a consentration of 2,5; 5; 7,5; 10; dan 12,5%. The results of variance analysis showed the optimum concentration of reeds activated carbon to reduce the levels of free fatty acids and colors absorbance in used cooking oil at a concentration of 7,5%. The percentage of decreasing levels of free fatty acids gorengan and pecel lele are 78.57% and 78.85%. Decrease in absorbance of gorengan color from 1,792% to 0,384% and the pecel lele color absorbance from 2,521 to 0,515. Keywords : Activated Carbon,Color, Free Fatty Acid, Reeds, and Used Cooking Oil.